(untitled) (Journal of Oriental Studies, 2017)
The article discusses the formation of the Iraqtheater. Theater ofIraq also took place to the efforts of national authors. Appeared alongwith the theater dramaturgy highlighted the social, historical problems ofIraq society in the twentieth century.